Budżetowanie kosztów jako instrument zarządzania kosztami w zakładzie ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Budgeting as one of Instruments in Cost Management in Insurance Company, 2007)
Cost management is a very important part of management in each company, especially in insurance companies which should concentrate on reaching satisfied results. One of the solutions in making management process better is responsible accounting with budgeting and separating canters. Costs' budgeting depends on kind of costing system which insurance company had applied. There are four kinds of costing systems which could be used in costs calculation in insurance companies: variable costing, activity based costing, kaizen costing and life cycle costing. Budgeting convention should be adjusted to the chosen costing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 98-105